Patient with Foreign Accent Syndrome in Post Infarct Thrombotic Stroke: A Case Report - Firstiafina Tiffany; Ira Ristinawati; Shafira Nur Hanifa (Magna Neurologica, 2024)
Background: Stroke is the second leading cause of death in the world and is the leading cause of disability worldwide. One of the disabilities is language disorder. Foreign Accent Syndrome (FAS) is a clinical condition associated with a noticeable change of accent, that could affect verbal communication and social interaction skills. By identifying this case earlier, we hope that the patient’s activity daily living is less disrupted. Case: A 54-year-old woman presented with right limb weakness and tingling, along with a change in speech accent from Javanese to Madurese, despite no prior exposure to Madurese. Neurobehavioral examination revealed language and memory disturbances, and MRI showed cerebral infarction in the bilateral hippocampi, small vessel ischemia in the bilateral frontal lobes, and corona radiata. Discussion: The accent change, known as FAS that was experienced by the patients are thought to be due to neurological causes, which was stoke. In a study using a lesion network mapping approach concluded that the lesion causing accent disorder was located within a single network in the bilateral frontal lobe. In line with the existing theory, the MRI results in this patient showed ischemia in the blood vessels of the bilateral frontal lobes. Conclusion: Clinical symtoms related to stroke depending on the location of the lesion. The accent change in this patient, known as Foreign Accent Syndrome (FAS), is believed to be caused by stroke affecting the bilateral frontal lobes. Early recognition of FAS can help reduce disruptions in communication and social interactions.